Use of paired serum samples for serodiagnosis of typhoid fever. - House, D; Chinh, N; Diep, T; Parry, C; Wain, J; Dougan, G; White, N; Hien, T; Farrar, J (2005)
Using an enzyme-linked immunosorbent assay we demonstrate that, in adult patients with typhoid fever, the sensitivity of a serological test based on the detection of anti-lipopolysaccharide immunoglobulin G is increased when used with paired serum samples taken 1 week apart.